Financial incentives to improve glycemic control in African American adults with type 2 diabetes: a pilot randomized controlled trial - Leonard E. Egede; Jennifer A. Campbell; Rebekah J. Walker; Aprill Z. Dawson; Joni S. Williams (BMC, 2021)
Abstract Background Financial incentives is emerging as a viable strategy for improving clinical outcomes for adults with type 2 diabetes. However, there is limited data on optimal structure for financial incentives and whether financial incentives are effective in African Americans with type 2 diabetes. This pilot study evaluated impact of three financial incentive structures on glycemic control in this population. Methods Sixty adults with type 2 diabetes were randomized to one of three financial incentive structures: 1) single incentive (Group 1) at 3 months for Hemoglobin A1c (HbA1c) reduction, 2) two-part equal incentive (Group 2) for home testing of glucose and HbA1c reduction at 3 months, and 3) three-part equal incentive (Group 3) for home testing, attendance of weekly telephone education classes and HbA1c reduction at 3 months. The primary outcome was HbA1c reduction within each group at 3 months post-randomization. Paired t-tests were used to test differences between baseline and 3-month HbA1c within each group. Results The mean age for the sample was 57.9 years and 71.9% were women. Each incentive structure led to significant reductions in HbA1c at 3 months with the greatest reduction from baseline in the group with incentives for multiple components: Group 1 mean reduction = 1.25, Group 2 mean reduction = 1.73, Group 3 mean reduction = 1.74. Conclusion Financial incentives led to significant reductions in HbA1c from baseline within each group. Incentives for multiple components led to the greatest reductions from baseline. Structured financial incentives that reward home monitoring, attendance of telephone education sessions, and lifestyle modification to lower HbA1c are viable options for glycemic control in African Americans with type 2 diabetes. Trial registration Trial registration: NCT02722499 . Registered 23 March 2016, url.